An empirical analysis of price setting behaviour in the Netherlands in the period 1998-2003 using micro data - Nicole Jonker; Carsten Folkertsma; Harry Blijenberg (European Central Bank (ECB), 2004)
In this paper we examine pricing behaviour of retail firms in the Netherlands during 1998-2003 using a large database with monthly price quotes of 49 articles, representing different product types. We have conducted this study in order to gain in sight in the degree of nominal rigidity of consumer prices in the Netherlands. We find that prices of energy and unprocessed food are most flexible, whereas prices of services are stickiest. A multivariate analysis shows that firm size matters with prices being stickiest in small firms and most flexible in large firms and in retail firms consisting of the owners only. Furthermore, we investigate pass-through effects of VAT changes in prices. We find that VAT increases are almost completely passed on to consumers. Finally, there is some evidence indicating that pricing behaviour of retail firms was different during the introduction of the euro than in the period directly preceding it.
Keywords: E31; D49; C41; 330; Cox regression; frequency of price change; nominal rigidity of prices